Lignin and lignans as renewable raw materials : chemistry, technology and applications /: chemistry, technology and applications. (2015) - Calvo-Flores, Francisco G; Dobado Jiménez, José A; Garcia, Joaquín I; Martín-Martínez, Francisco J
No abstract available